2013
DOI: 10.1021/jp402770p
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ti Intermetallic Catalysts on Hydrogen Storage Properties of Magnesium Hydride

Abstract: Magnesium hydride is a promising candidate for solid-state hydrogen storage and thermal energy storage applications. A series of Ti-based intermetallic alloy (TiAl, Ti3Al, TiNi, TiFe, TiNb, TiMn2, and TiVMn)-doped MgH2 materials were systematically investigated in this study to improve its hydrogen storage properties. The dehydrogenation and hydrogenation properties were studied by using both thermogravimetric analysis and pressure–composition–temperature (PCT) isothermal to characterize the temperature of deh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
97
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 142 publications
(102 citation statements)
references
References 46 publications
4
97
0
Order By: Relevance
“…Our calculations show that the Mg-Ti interfacial zone appears as negative hydrogen adsorption energy [18]. The hydrogen storage properties can be improved by Ti-Mn intermetallics, in which the TiMn 2 participates in the de/hydrogenation process with remarkable hydrogenation kinetics at room temperature [19]. Previously, we found the formation of TiH 2 due to the strong bonding interactions between Ti and its neighboring H atoms and the great distortion of Mn alloyed MgH 2 will help to improve the dehydrogenation property of MgH 2 [20].…”
Section: Introductionmentioning
confidence: 86%
“…Our calculations show that the Mg-Ti interfacial zone appears as negative hydrogen adsorption energy [18]. The hydrogen storage properties can be improved by Ti-Mn intermetallics, in which the TiMn 2 participates in the de/hydrogenation process with remarkable hydrogenation kinetics at room temperature [19]. Previously, we found the formation of TiH 2 due to the strong bonding interactions between Ti and its neighboring H atoms and the great distortion of Mn alloyed MgH 2 will help to improve the dehydrogenation property of MgH 2 [20].…”
Section: Introductionmentioning
confidence: 86%
“…Details of the milling method and properties of the as-milled product can be found in our previous publication [16]. After milling, 50 g of TiMn 2 catalyzed MgH 2 was mixed with 5 wt.% expanded graphite (ENG).…”
Section: Materials Preparationmentioning
confidence: 99%
“…Extensive research efforts, including optimization of the hydride materials, have been reported elsewhere [12,16,19]. Initially, in order to verify thermodynamic compatibility of the two hydride candidate materials, hydrogen equilibrium pressures of MgH 2 and TiMnV were characterized using a Sievert-type apparatus (PCT-Pro 2000).…”
Section: Hydride Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…This impetus led to the current work which investigated a simple route for the synthesis of isolated LiAlH 4 nanoparticles and their stabilization for hydrogen cycling through a core-shell approach, with Ti acting as a shell facilitating the retention of molten LiAlH 4 upon dehydrogenation as well as a "gateway" for hydrogen absorption/desorption. Ti based additives have been widely studied via top-down ball milling for LiAlH 4 , as well as with other alanate systems e.g., NaAlH 4 and Mg(AlH 4 ) 2 with promising results, i.e., much improved hydrogen storage properties [21][22][23][24][25][26]. Indeed, Kojima et al determined the catalytic effects of various metal chlorides on LiAlH 4 , and revealed their positive effects in terms of hydrogen release in the order of TiCl 3 > ZrCl 4 > VCl 3 > NiCl 2 > ZnCl 2 [27].…”
Section: Introductionmentioning
confidence: 99%